The Importance of Early Diagnosis, Education and Physical Activity in Children with Autism - Savucu, Yüksel (İbrahim ERDEMİR, 2020)
Autism is considered to come about because of a process that affects the structures or the functions of the brain and the nervous system. The prevalent opinion is that autism can have a genetic basis and is triggered by environmental factors. In this study, it was emphasized the importance of early diagnosis, education and physical activities on autistic children by reviewing the literature. Although a diagnostic criterion of children with autism does not involve incapacitating to cover motor skills, studies indicated that motor deficits and delays in children with autism are possible. It is generally known that regular physical exercises and social activities promote the physical and mental health of these children. The difficulties with social interactions that children with autism experience mainly pertain to a lack of understanding of the behaviour of others resulting from an inability to adequately interpret consider or react to the social and emotional signals of others as communicated through eye contact and facial expressions. Individuals with autism are ensured to be in social life thanks to early diagnosis, control of autism, appropriate training and rehabilitation programs. Especially for these people, physical activity is one of the most effective ways of establishing healthy relationships not only at home but also in all areas of life at the stage of education and rehabilitation.

Otizm, beynin ve sinir sisteminin yapılarını veya işlevlerini etkileyen bir sürecin sonucu olarak düşünülür. Yaygın görüş otizmin genetik bir temeli olabileceği ve çevresel faktörler tarafından tetiklenebileceğidir. Bu çalışmada literatür taraması yapılarak otizmli çocuklarda erken tanı, eğitim ve fiziksel aktivitelerin önemi vurgulanmaya çalışılmıştır. Otizmli çocukların tanı kriteri motor becerilerini kapsayacak şekilde yetersiz olmamasına rağmen, çalışmalar otizmli çocuklarda motor bozuklukların ve gecikmelerin mümkün olduğunu göstermiştir. Genellikle düzenli fiziksel egzersizlerin ve sosyal aktivitelerin bu çocukların fiziksel ve zihinsel sağlığını desteklediği bilinmektedir. Otizmli çocukların yaşadığı sosyal etkileşimlerdeki zorluklar, esas olarak, göz teması ve yüz ifadeleri aracılığıyla iletilen diğerlerinin sosyal ve duygusal sinyallerini yeterince yorumlayamama, değerlendirememe veya bunlara tepki vermeme nedeniyle başkalarının davranışlarını anlama eksikliğiyle de ilgili olabilmektedir. Erken teşhis, otizmin kontrol altına alınması, uygun eğitim ve rehabilitasyon programları sayesinde otizmli bireylerin toplumsal yaşam içinde olmaları sağlanır. Özellikle bu insanlar için, eğitim ve rehabilite aşamasında sadece evde değil hayatın her alanında sağlıklı ilişkiler kurabilmeleri açısından fiziksel aktivite en etkili yollardan biridir.
Otizmli Çocuklarda Erken Tanı, Eğitim ve Fiziksel Aktivitenin Önemi
Keywords: Sports Medicine; Spor Hekimliği